O24 Confirming gc naat results: is it always necessary?. (18th May 2015) - Alexander, Sarah; Patel, Hemanti; Warwick, Simon; Fifer, Helen
Abstract : Introduction: Current guidance recommends that all specimens testing positive using a N. gonorrhoeae Nucleic Acid Amplification Test (GC NAAT) be confirmed using a second test with an alternative target, in order to achieve a positive predictive value above 90%. Aim: To determine rates of GC NAAT confirmations by primary screening test and specimen site. Methods: 994 specimens which were GC NAAT positive at local laboratories were sent for confirmation using an in-house multiplex PCR with Por A and opa gene targets. A correlation between the confirmatory real-time PCR results, specimen site and GC screening NAAT was undertaken. For the purposes of this analysis equivocal results were regarded as positive and inhibited results were excluded. Results: Overall, 57% of specimens examined could be confirmed as GC positive using the in-house real-time PCR test (Table 1). Discussion: High rates of confirmation can be achieved when examining genital, rectal and urine specimens irrespective of the GC screening NAAT. However >90% confirmatory rates were only achieved when examining male urine specimens which had been screened using the Probetec and Cobas Amplicor tests, although caution should be applied if extrapolating this data to low prevalence settings. Poor confirmation rates from throat specimens is probably due to cross-reactivity with commensal Neisseria, and highlights confirmation is essential when testing these samples.